2016
DOI: 10.1155/2016/1902151
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge of Stroke Risk Factors among Stroke Survivors in Nigeria

Abstract: Background. Knowledge of stroke risk factors is expected to reduce the incidence of stroke—whether first-ever or recurrent. This study examined knowledge of stroke risk factors and its determinants among stroke survivors. Methods. A cross-sectional survey of consenting stroke survivors at two physiotherapy facilities in Nigeria was carried out. Sociodemographic and clinical data were obtained and knowledge of stroke risk factors (defined as the ability to mention at least one correct risk factor) was assessed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
16
2
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 22 publications
5
16
2
3
Order By: Relevance
“…The mean score of knowledge was 22 out of 45, reflecting a suboptimal or below average level of awareness among both high and low risk individuals. This is similar to other studies done in African countries where predictors of good knowledge included male sex and educational status [ 7 , 12 ], while areas of poor knowledge included risk factors [ 13 ] and symptoms [ 12 ]. However, some studies reported contradicting results of good knowledge among high risk patients [ 8 ].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The mean score of knowledge was 22 out of 45, reflecting a suboptimal or below average level of awareness among both high and low risk individuals. This is similar to other studies done in African countries where predictors of good knowledge included male sex and educational status [ 7 , 12 ], while areas of poor knowledge included risk factors [ 13 ] and symptoms [ 12 ]. However, some studies reported contradicting results of good knowledge among high risk patients [ 8 ].…”
Section: Discussionsupporting
confidence: 88%
“…Rapid identification, quick transfer to medical care and immediate and appropriate medical care are key factors in improving outcome of stroke [ 6 ]. Awareness about stroke amongst patients, caretakers and medical staff has been studied in some African countries [ 3 , 7 - 13 ], most of which revealed a generally poor level of awareness. Locally, levels of stroke awareness amongst medical staff, patients and caretakers in Sudan are unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies showed contrasting outcomes, such as in Nigeria, where stroke survivors with a tertiary educational level were 48 time more likely to be knowledgeable about stroke and more compliant to treatment than those with lower education. 34 This was in agreement with other large cohort-sized surveys relying on open-ended questions in Norway and China. 35,36 However, Saengsuwan et al 25 failed to reveal a significant impact of education on stroke knowledge and adherence to post-stroke therapies, possibly due to the small sample size (140 patients).…”
Section: Methods Design and Settingsupporting
confidence: 90%
“…The gender of the participants in this study was virtually evenly distributed among male and female participants constituting 55% and 45% respectively, which is in line with findings of several studies in both the developed and the developing countries in which even distribution of participants gender was reported among stroke survivors (Oros et al, 2016). The mean age of the participants was 55.16 ± 10.01 and the range was 23 -83 years, which is similar to the mean age of 55.97 ± 9.56 years reported in a study by Vincent-Onabajo & Moses (2016). Majority of the participants were married (62%) as were those employed (51%) which is in line with findings by Vincent-Onabajo and Adamu (2014).…”
Section: Socio-demographic and Clinical Characteristics Of The Particsupporting
confidence: 89%